Worker directors: a German product that didn't export? - John T. Addison; Claus Schnabel (Institute for the Study of Labor (IZA), 2009)
Despite its lack of attractiveness to other countries, the German system of quasi-parity codetermination at company level has held up remarkably well. We recount the theoretical arguments for and against codetermination and survey the empirical evidence on the effects of the institution, tracing the three phases of a still sparse literature. Recent findings hold out the prospect that good corporate governance might include employee representation by virtue of the monitoring function and the reduction in agency costs, while yet cautioning that the optimal level of representation is likely below parity. And although the German system may be better than its reputation among foreigners, it might have to adapt to globalization and the availability of alternative forms of corporate governance in the EU.
urn:nbn:de:101:1-20090119140
Keywords: J50; 330; Codetermination; board-level employee representation; firm performance; Germany; Mitbestimmung; Arbeitsdirektoren; Corporate Governance; Unternehmensentwicklung; Globalisierung; Deutschland